INDIVIDUAL AND PROFESSIONAL VALUES OF NURSE PRACTITIONERS - Sudraba, Velga; Briede, Ieva (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Individual and professional values of nurses enhance the psychological wellbeing of healthcare professionals, enabling them to do professional and proficient work and also reducing the risk of burnout. The aim of the study was to investigate individual and professional values of nurse practitioners and the relationship of these values to socio-demographic data. The study involved 163 nurses aged 22–70 years (41.6 + 12.64) with 99.8% women. Respondents were interviewed in two hospitals in Riga in 2019. Permission from Rīga Stradiņš University Ethics Committee was obtained to do the study. Two surveys were used in the research: (1) Rokeach Value Survey and (2) Nurses Professional Values Scale–Three (NPVS–3). There was no statistically significant correlation between socio-demographic data of nurses and their professional values. The most evident professional value group for nurses was care. The Rokeach scale listed physical and mental health as a priority of all terminal values with an average rate 3.8. On the other hand, happiness of others ranks as the last priority in the list of terminal values with an average rating of 14.5. At the top of the instrumental values was honesty with an average rating of 6.3. Intolerance toward the drawbacks of oneself and other people concludes the list with an average rating of 15.0.